Ocean Acidification Alters the Predator – Prey Relationship Between Hydrozoa and Fish Larvae - Spisla, Carsten; Taucher, Jan; Sswat, Michael; Wunderow, Hennrike; Kohnert, Peter; Clemmesen, Catriona; Riebesell, Ulf (Frontiers in Marine Science, 2022)
Anthropogenic CO2 emissions cause a drop in seawater pH and shift the inorganic carbon speciation. Collectively, these changes are summarized under the term ocean acidification (OA). Research of OA effects on predatory plankton, e.g. Hydrozoa and fish larvae as well as their interaction in complex natural communities remains scarce. Because Hydrozoa can be serious competitors and predators on other higher-level predators like fish, changes in their abundances may have significant consequences for marine food webs and ecosystem services. To investigate the interaction between Hydrozoa and fish larvae influenced by OA, we enclosed a natural plankton community in the Raunefjord, Norway, for 53 days in eight ≈ 58 m³ pelagic mesocosms. CO2 levels in four mesocosms were increased to ≈ 2000 µatm pCO2, while the other four served as untreated controls. OA induced changes at the top of the food web were studied by following ≈2000 larvae of Atlantic herring (Clupea harengus) hatched inside each mesocosm during the first week of the experiment, and a Hydrozoa population that had already established inside the mesocosms. Under OA, we detected a 20% higher abundance of hydromedusae staged jellyfish, but a 25% lower biomass. At the same time, survival rates of Atlantic herring larvae were higher under OA (ambient pCO2: 0.1%, high pCO2: 1.7%) in the final phase of the study. These results indicate that higher herring larvae survival was most likely shaped by a decrease in predation pressure shortly after hatch, when hydromedusae abundance was lower in the OA treatment compared to the ambient. We conclude that the observed changes in the Hydrozoa – fish relationship were driven by indirect food-web mediated OA effects, based on significant changes in the phyto-, micro-, and mesoplankton community under high pCO2. Ultimately, the observed immediate consequences of these changes for fish larvae survival and the balance of the Hydrozoa – fish larvae predator – prey relationship contain important implications for the functioning of oceanic food webs.